Supercooled preservation of cultured primary rat hepatocyte monolayers - Gokaltun, Aslihan; Asik, Eda; Byrne, Delaney; Yarmush, Martin L.; Usta, O. Berk (Frontiers in Bioengineering and Biotechnology, 2024)
Supercooled preservation (SCP) is a technology that involves cooling a substance below its freezing point without initiating ice crystal formation. It is a promising alternative to prolong the preservation time of cells, tissues, engineered tissue products, and organs compared to the current practices of hypothermic storage. Two-dimensional (2D) engineered tissues are extensively used in in vitro research for drug screening and development and investigation of disease progression. Despite their widespread application, there is a lack of research on the SCP of 2D-engineered tissues. In this study, we presented the effects of SCP at -2 and -6 o C on primary rat hepatocyte (PRH) monolayers for the first time and compared cell viability and functionality with cold storage (CS, +4 o C). We preserved PRH monolayers in two different commercially available solutions: Hypothermosol-FRS (HTS-FRS) and the University of Wisconsin (UW) with and without supplements (i.e., polyethylene glycol (PEG) and 3-O-Methyl-Α-D-Glucopyranose (3-OMG)). Our findings revealed that UW with and without supplements were inadequate for the short-term preservation of PRH monolayers for both SCP and CS with high viability, functionality, and monolayer integrity. The combination of supplements (PEG and 3-OMG) in the HTS-FRS solution outperformed the other groups and yielded the highest viability and functional capacity. Notably, PRH monolayers exhibited superior viability and functionality when stored at -2°C through SCP for up to 3 days compared to CS. Overall, our results demonstrated that SCP is a feasible approach to improving the short-term preservation of PRH monolayers and enables readily available 2D-engineered tissues to advance in vitro research. Furthermore, our findings provide insights into preservation outcomes across various biological levels, from cells to tissues and organs, contributing to the advancement of bioengineering and biotechnology.